CD4+ T Cell‐Released Extracellular Vesicles Potentiate the Efficacy of the HBsAg Vaccine by Enhancing B Cell Responses. Issue 23 (30th September 2019) - Lu, Jian; Wu, Jing; Xie, Feiting; Tian, Jie; Tang, Xinyi; Guo, Hongye; Ma, Jie; Xu, Ping; Mao, Lingxiang; Xu, Huaxi; Wang, Shengjun
Abstract: T cells secrete bioactive extracellular vesicles (EVs), but the potential biological effects of CD4 + T cell EVs are not clear. The main purpose of this study is to investigate the effects of CD4 + T cell–derived EVs on B cell responses and examine their role in antigen‐mediated humoral immune responses. In this study, CD4 + T cell EVs are purified from activated CD4 + T cells in vitro. After immunization with the Hepatitis B surface antigen (HBsAg) vaccine, CD4 + T cell EVs‐treated mice show stronger humoral immune responses, which is indicated by a greater Hepatitis B surface antibody (HBsAb) level in serum and a greater proportion of plasma cells in bone marrow. In addition, it is found that EVs released from activated CD4 + T cells play an important role in B cell responses in vitro, which significantly promote B cell activation, proliferation, and antibody production. Interestingly, antigen‐specific CD4 + T cell EVs are found to be more efficient than control EVs in enhancing B cell responses. Furthermore, it is shown that CD40 ligand (CD40L) is involved in CD4 + T cell EVs‐mediated B cell responses. Overall, the results have demonstrated that CD4 + T cell EVs enhance B cell responses and serve as a novel immunomodulator to promote antigen‐specific humoral immune responses. Abstract : CD4 + T cells release bioactive extracellular vesicles. CD4 + T cells extracellular vesicles (EVs) can enhance B cell responses by CD40 ligand (CD40L), which significantly promote B cell activation, proliferation, and antibody production in vitro. In addition, the application of CD4 + T cell EVs further promotes antigen‐specific humoral immune responses in Hepatitis B surface antigen (HBsAg)‐immunized mice.